Similar long-term survival of consecutive in-hospital and out-of-hospital cardiac arrest patients treated with targeted temperature management - Engsig, Magaly; Søholm, Helle; Folke, Fredrik; Gadegaard, Peter; Wiis, Julie; Molin, Rune; Mohr, Thomas; Engsig, Frederik (Clinical epidemiology, 2016)
The long-term survival of in-hospital cardiac arrest (IHCA) patients treated with targeted temperature management (TTM) is poorly described. The aim of this study was to compare the outcomes of consecutive IHCA with out-of-hospital cardiac arrest (OHCA) patients treated with TTM. Retrospectively collected data on all consecutive adult patients treated with TTM at a university tertiary heart center between 2005 and 2011 were analyzed. Primary endpoints were survival to hospital discharge and long-term survival. Secondary endpoint was neurological outcome assessed using the Pittsburgh cerebral performance category (CPC). A total of 282 patients were included in this study; 233 (83%) OHCA and 49 (17%) IHCA. The IHCA group presented more often with asystole, received bystander cardiopulmonary resuscitation (CPR) in all cases, and had shorter time to return of spontaneous circulation (ROSC). Survival to hospital discharge was 54% for OHCA and 53% for IHCA (adjusted odds ratio 0.98 [95% confidence interval CI; 0.43-2.24]). Age ≤60 years, bystander CPR, time to ROSC ≤10 min, and shockable rhythm at presentation were associated with survival to hospital discharge. Good neurologic outcome among survivors was achieved by 86% of OHCA and 92% of IHCA ( =0.83). After a median follow-up time of >5 years, 83% of OHCA and 77% of IHCA were alive (adjusted hazard ratio [HR] 1.51 [95% CI; 0.59-3.91]). Age ≤60 years was the only factor associated with long-term survival (adjusted HR 2.73 [95% CI; 1.36-5.52]). There was no difference in short- and long-term survival and no difference in neurologic outcome to hospital discharge between IHCA and OHCA patients treated with TTM despite higher frequency of asystole in IHCA.